ENHANCING INTERNAL FINANCIAL AND MANUFACTURING COST MEASUREMENT AND ANALYSIS: AN ANALYTICAL STUDY OF MODERN FINANCIAL COST METHODS - Badawi Abdelrhman Musa, Aisha; Ibrahim Ahamed Mohamed, Manal (The journal of contemporary issues in business and government, 2025)
This study has applied descriptive approach to study Kenana Sugar Company Limited's accounts and financial departments, involving 87 male and female employees. A random sampling method selected 45 individuals, who were analyzed using questionnaires. The results showed positive results. The demographic, academic, and professional background of the participants is also compared to reveal some interaction with performance and career advancement. The sample is slightly older and almost all of the participants work mid-career level; most of the participants belong to accounting and finance fields. The study found that 75% of participants aged 36- 45 years and 81.58% held a Bachelor's degree had no significant differences in performance based on academic achievement or work experience. However, the research faces challenges in generalizing to a wider population and suggests expanding the scope of participants by specializations and career phases.